Extracranial 125I Seed Implantation Allows Non-invasive Stereotactic Radioablation of Hippocampal Adult Neurogenesis in Guinea Pigs - Lily Wan (Frontiers Media S.A., 2021)
Adult hippocampal neurogenesis (AHN) is important for multiple cognitive functions. We sort to establish a minimal or non-invasive radiation approach to ablate AHN using guinea pigs as an animal model. 125I seeds with different radiation dosages (1.0, 0.8, 0.6, 0.3 mCi) were implanted unilaterally between the scalp and skull above the temporal lobe for 30 and 60 days, with the radiation effect on proliferating cells, immature neurons, and mature neurons in the hippocampal formation determined by assessment of immunolabeled (+) cells for Ki67, doublecortin (DCX), and neuron-specific nuclear antigen (NeuN), as well as Nissl stain cells. Spatially, the ablation effect of radiation occurred across the entire rostrocaudal and largely the dorsoventral dimensions of the hippocampus, evidenced by a loss of DCX+ cells in the subgranular zone (SGZ) of dentate gyrus (DG) in the ipsilateral relative to contralateral hemispheres in reference to the 125I seed implant. Quantitatively, Ki67+ and DCX+ cells at the SGZ in the dorsal hippocampus were reduced in all dosage groups at the two surviving time points, more significant in the ipsilateral than contralateral sides, relative to sham controls. NeuN+ neurons and Nissl-stained cells were reduced in the granule cell layer of DG and the stratum pyramidale of CA1 in the groups with 0.6-mCi radiation for 60 days and 1.0 mCi for 30 and 60 days. Minimal cranial trauma was observed in the groups with 0.3– 1.0-mCi radiation at 60 days. These results suggest that extracranial radiation with 125I seed implantation can be used to deplete HAN in a radioactivity-, duration-, and space-controllable manner, with a “non-invasive” stereotactic ablation achievable by using 125I seeds with relatively low radioactivity dosages.